PRODUKTIVITAS DAN KEUNTUNGAN USAHATANI PADI SAWAH TADAH HUJAN DI DESA BARUH BAHINU DALAM KECAMATAN PARINGIN SELATAN KABUPATEN BALANGAN - Yozef Agus Suratman, Yan (Fakultas Pertanian UVAYA Banjarmasin, 2022)
This research aims are: (1). Knowing the technical description of rainfeeded paddy farming carried out by farmers; (2) knowing the costs, revenues, profit, and labor productivity of paddy farming Baruh Bahinu Dalam Village, South Paringin district, Balangan Regency. This research uses survey method with observation technique. The sampling method uses a simple random sampling. The population of farmers who rain feeded paddy is 150 people, then 20% of the total farmers in this village, 30 farmers are used as respondent farmers. The result of the research is that the average land area used by farmers is 0.57 hectares (19.97 wholesale) and the status of land ownership is property rights. The production of paddy farming in Baruh Bahinu Dalam Village was 2,350.33 kg/farmer or 4,123.39 kg/hectare. The average cost is IDR 3,151,705.38 /farmer, the average revenue is IDR 18,802,640.00 /farmer and the average profit is IDR 15,650,934.61/farmer. Labor productivity index is IDR 508,316,84/ HOK, compared to the wage of labor per HOK, it means that the paddy farming workforce is productive